The prevalence of respectful maternity care during childbirth and its determinants in Ethiopia: A systematic review and meta-analysis - Aklilu Habte; Aiggan Tamene; Demelash Woldeyohannes; Fitsum Endale; Biruk Bogale; Addisalem Gizachew (PLoS ONE, 2022)
Background Respectful maternity care is the provision of woman-centered health care during childbirth that is friendly, abuse-free, timely, and discrimination-free. Although several epidemiological studies on the magnitude and determinants of Respectful maternity care in Ethiopia have been conducted, the results have been inconsistent and varied. This makes drawing equivocal conclusions and evidence at the national level harder. Hence, this systematic review and meta-analysis aimed at estimating the pooled prevalence of respectful maternity care and its determinants in Ethiopia. Methods Studies conducted from 2013 to June 30, 2022, were searched by using PubMed, Google Scholar, Science Direct, Scopus, ProQuest, Web of Science, Cochrane Library, and Direct of Open Access Journals. Searching was carried out from May 15- June 30, 2022. In total, sixteen studies were considered in the final analysis. The data were extracted using Microsoft Excel and analyzed using STATA 16 software. The methodological quality of included studies was assessed by using Joanna Briggs Institute’s critical appraisal checklist for prevalence studies. To estimate the pooled national prevalence of respectful maternity care, a random effect model with a DerSimonian Laird method was used. To assess the heterogeneity of the included studies, the Cochrane Q test statistics and I2 tests were used. To detect the presence of publication bias, a funnel plot and Begg’s and Egger’s tests were used. Results Sixteen studies were eligible for this systematic review and meta-analysis with a total of 6354 study participants. The overall pooled prevalence of respectful maternity care in Ethiopia was 48.44% (95% CI: 39.02–57.87). Receiving service by CRC-trained health care providers [AOR: 4.09, 95% CI: 1.73, 6.44], having ANC visits [AOR: 2.34, 95% CI: 1.62, 3.06], planning status of the pregnancy [AOR = 4.43, 95% CI: 2.74, 6.12], giving birth during the daytime [AOR: 2.61, 95% CI: 1.92, 3.31], and experiencing an obstetric complication[AOR: 0.46, 95% CI: 0.30, 0.61] were identified as determinants of RMC. Conclusion As per this meta-analysis, the prevalence of respectful maternity care in Ethiopia was low. Managers in the health sector should give due emphasis to the provision of Compassionate, Respectful, and Care(CRC) training for healthcare providers, who work at maternity service delivery points. Stakeholders need to work to increase the uptake of prenatal care to improve client-provider relationships across a continuum of care. Human resource managers should assign an adequate number of health care providers to the night-shift duties to reduce the workload on obstetric providers.